PENGOPTIMALAN LUAS AREAL PERTANIAN DESA KINARUM DAN DESA MARINDI KABUPATEN TABALONG - Rusidah Rusidah (Lambung Mangkurat University Press, 2012)
Kinarum River which is located in Tabalong Regency has not been used for farming. There is a vast farming area in the Kinarum River Basin which still heavily depends on the water from rain. Water from the river is only used for irrigation in three villages, namely Kinarum village, Pengelak village and Marindi village, although it has the potential to irrigate a bigger area. To increase the potential and the area of farm fields in the Kinarum River Basin, Water Scale analysis was carried out, while the water availability calculated using Primary Debit Method. The water availability analysis was based on daily or monthly river debit in a period longer than a decade. By using rain spill connection mathematical model, the potential evapotranspiration was obtained. The chosen rain-debit connection models with a monthly interval were Mock and NRECA methods, which resulted in the Primary Debit (Q80). Water Scale analysis of Kinarum River Basin used the water availability as Input (I) and the need as Output (O). The water availability or the primary debit (Q80) per year based on Mock Method and NRECA Method is respectively 0.831 m3/s and 1.337 m3/s. Mock method gives the best approximation (0.822 m3/s ) for the historic debit. Hence, the primary debit (Q80) is 0.831 m3/s. EventhoughKinarum River Basin has irrigated 300 hectares of farming land, it still has a capacity to extend its irrigation area up to 1,060 hectares by applying optimal planting pattern 5 (namely rice-crops-crops)